2009
DOI: 10.1021/ja9021478
|View full text |Cite
|
Sign up to set email alerts
|

Full Color Stop Bands in Hybrid Organic/Inorganic Block Copolymer Photonic Gels by Swelling−Freezing

Abstract: We report a facile way of fabricating hybrid organic/inorganic photonic gels by selective swelling and subsequent infiltration of SiO(2) into one type of lamellar microdomain previously self-assembled from modest-molecular-weight block copolymers. Transparent, in-plane lamellar films were first prepared by assembly of polystyrene-block-poly(2-vinylpyridine) (PS-b-P2VP), and subsequently the P2VP domains were swollen with a selective solvent, methanol. The swollen structures were then fixated by synthesizing Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 20 publications
0
103
0
1
Order By: Relevance
“…[127][128][129][130][131][132] The self-assembled polystyrene-block-poly(2-vinylpyridine) (PS-b-P2VP) polymer formed a simple 1D periodic lamellar structure via amphiphilic interactions, and the P2VP blocks were quaternized and crosslinked to form polyelectrolyte block gel layers (Figure 7c). [127,128] Aqueous solvents modulated the swelling/ deswelling behavior of the polyelectrolyte block gel layers, resulting in changes in both the polyelectrolyte block domain spacing and the refractive-index contrast; accordingly, the wavelengths of light that were reflected by the stop band shifted. In the human body, muscle sarcomere contains a large amount of actin and myosin, which display anisotropic liquid crystalline structures.…”
Section: Self-assemblymentioning
confidence: 99%
“…[127][128][129][130][131][132] The self-assembled polystyrene-block-poly(2-vinylpyridine) (PS-b-P2VP) polymer formed a simple 1D periodic lamellar structure via amphiphilic interactions, and the P2VP blocks were quaternized and crosslinked to form polyelectrolyte block gel layers (Figure 7c). [127,128] Aqueous solvents modulated the swelling/ deswelling behavior of the polyelectrolyte block gel layers, resulting in changes in both the polyelectrolyte block domain spacing and the refractive-index contrast; accordingly, the wavelengths of light that were reflected by the stop band shifted. In the human body, muscle sarcomere contains a large amount of actin and myosin, which display anisotropic liquid crystalline structures.…”
Section: Self-assemblymentioning
confidence: 99%
“…Previously, we have demonstrated that block copolymer lamellar structures are useful for creating tunable photonic crystals. [26][27][28][29][30] For instance, the lamellae assembled from polystyrene-b -quaternized poly(2-vinyl pyridine) (PS-b -QP2VP) exhibited strong refl ective colors when the QP2VP layers were selectively swollen with solvents. In this case, photonic stop bands (PSBs) varied with the extent of swelling, and which can be controlled by crosslinking density and the species of counter-anions pairing with pyridinium groups.…”
Section: Doi: 101002/adma201103767mentioning
confidence: 99%
“…[26][27][28][29] Briefl y, in-plane oriented lamellar fi lms were fi rst prepared by spin casting PS 57 -b -P2VP 57 solution (Number-average molecular weight (M n ) of each block is 57 × 10 3 g/mol and 57 × 10 3 g/mol for PS and P2VP respectively, PDI = 1.08, 6 wt% in propylene glycol monomethyl ether acetate) onto glass followed by annealing the fi lms in chloroform vapor at 50 ° C for 2 days. The thickness of the fi lms was controlled to ∼ 1 μ m. The P2VP blocks were then quaternized using iodomethane in hexane at 50 ° C for 24 hours.…”
Section: Doi: 101002/adma201103767mentioning
confidence: 99%
“…[17][18][19] Our group recently reported highly tunable photonic gels based on polystyrene-bquaternized poly(2-vinyl pyridine) (PS-b-QP2VP). [10][11][12][13][14][15][16] The swollen photonic gels found many applications including as an active component of reflective displays, memory and biosensors. Herein, we report block copolymer photonic gels as solvent sensor.…”
Section: -16mentioning
confidence: 99%